Integrated Water Quality Assessment Of Chhirapaani Reservoir Using Physicochemical Parameters And Wqi Approach - Manikpuri, Durgesh Das; Shrivastava, Shilpi (Journal of Neonatal Surgery, 2025)
Chhirapaani Reservoir in Kabirdham District, Chhattisgarh is a multi-use surface-water resource that supports irrigation, fisheries, and local domestic requirements; therefore, regular assessment of its water quality is essential for protecting public health and ensuring sustainable reservoir management. The present study provides a comprehensive evaluation of physicochemical and microbiological characteristics of the reservoir using standard laboratory analytical procedures and a criteria-based interpretative framework. The assessment is structured around the distinct seasonal hydrological conditions of central India, namely pre-monsoon concentration effects, monsoon-driven runoff inputs, and post-monsoon stabilization, as these seasonal processes strongly influence turbidity, nutrient levels, ionic composition, and oxygen-demanding loads in reservoir systems. To facilitate integrated interpretation and effective communication of overall water quality status, a Water Quality Index approach is employed with clear emphasis on transparent parameter selection, weighting, and classification. The results are presented through two structured tables: one focusing on individual parameter compliance and another summarizing the composite water quality index. The study is presented in a concise paragraph format to allow direct application of observed data without altering the analytical framework, making it suitable for both academic research and water-resource management applications.. ..